Peppermint essential oil extends the vase life of the cut Dendrobium orchid ‘White Sanan’ - Teerarak, M.; Saetiew, K.; Laosinwattana, C. (My University, 2023)
The vase life of cut orchid flowers is significantly extended by preservative solutions containing silver compounds. However, these compounds are toxic and require careful handling and disposal. As a result, the demand is increasing for natural preservation materials such as plant essential oils as they are biodegradable, ecofriendly, and safe alternatives for enhancing vase life and postharvest cut flower quality. The objective of this investigation was to study the effects of an emulsion of glucose and peppermint essential oil on vase life and postharvest quality of the popular cut Dendrobium orchid ‘White Sanan’. The orchids were preserved in vase solutions of distilled water or 4% glucose + 0.005-0.02% peppermint essential oil. The essential oil treatment increased the vase life of the flowers and the inflorescences by more than 6 days longer than the control treatment. The combination of glucose and peppermint essential oil increased water uptake and the fresh weight of cut orchids and delayed wilting time and abscission of floral buds and open florets. Moreover, treatment with the vase solution containing 4% glucose + 0.005% peppermint essential oil resulted in the highest bud opening rate (86.9%). Our results suggest that applying 4% glucose and 0.005-0.02% peppermint essential oil is especially effective as a preservative solution for the Dendrobium orchid ‘White Sanan’.
Keywords: cut flower; floral preservative; longevity; water uptake